IMPLIKASI PENDEKATAN EKSISTENSIAL DALAM MENGURANGI PENYALAHGUNAAN NARKOBA DI KALANGAN REMAJA - Maulana Riqfi Zaein; Yovityo Azitya Kurnianto; Devi Ratnasari (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
Focusing on personal growth and meaning-making, the existential approach can serve as a valuable complement to traditional addiction treatment methods, ultimately contributing to more effective strategies for combating adolescent drug abuse. Among them, many adolescents engage in deviant behavior because they are carried away by their peers. The purpose of this study is to increase individual awareness of their existence and potential, so that they can make better choices. The method used is qualitative with a literature study. Literature study is a way to solve problems by tracing previously written sources. In other words, the term literature study is also very familiar with the term library study. The results of the study indicate that the existential approach can contribute to reducing drug abuse among adolescents by emphasizing self-awareness and individual responsibility. Through existential counseling, adolescents can understand their life choices and overcome feelings of emptiness or alienation that often trigger drug abuse. The discussion in this article is the implications of the existential approach in reducing drug abuse among adolescents. Drug use and addictive substances continue to pose significant challenges for young people, understanding the underlying existential struggles that contribute to addiction is very important. Using qualitative research methods, this study investigated the experiences of adolescents who had been involved in an existential-based intervention aimed at addressing their substance use. The findings of the study contained 6 findings, namely (1). Definition of the existential approach and drug abuse, (2). factors of drug abuse, (3). the purpose of existential therapy, (4). the relationship of the existential approach to reducing drug abuse, The findings revealed that existential therapy fosters self-awareness, personal responsibility, and a deeper understanding of the meaning of life, which are important for overcoming addiction. This article highlights the potential for integrating existential principles into existing treatment frameworks as a means to empower adolescents on their recovery journey. By a. In addition, building a supportive environment, including social support and positive activities, can help adolescents develop healthy coping skills, reducing the risk of drug use.